2022
DOI: 10.1038/s41586-022-04801-2
|View full text |Cite|
|
Sign up to set email alerts
|

Potentiating adoptive cell therapy using synthetic IL-9 receptors

Abstract: Synthetic receptor signalling has the potential to endow adoptively transferred T cells with new functions that overcome major barriers in the treatment of solid tumours, including the need for conditioning chemotherapy1,2. Here we designed chimeric receptors that have an orthogonal IL-2 receptor extracellular domain (ECD) fused with the intracellular domain (ICD) of receptors for common γ-chain (γc) cytokines IL-4, IL-7, IL-9 and IL-21 such that the orthogonal IL-2 cytokine elicits the corresponding γc cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 60 publications
0
68
0
Order By: Relevance
“…In particular, the ortho IL-2 approach 47 may control for previous limitations by delivering Stat5 inducing signals only to the cells of interest. 61…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the ortho IL-2 approach 47 may control for previous limitations by delivering Stat5 inducing signals only to the cells of interest. 61…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the orthoIL-2 approach 47 may control for previous limitations by delivering Stat5 inducing signals only to the cells of interest. 61 Since the discovery of the distinct epigenetic wiring of TEX that limits re-differentiation upon PD-1 blockade, 25,40 developing approaches to reprogram the epigenetics of TEX has been a major goal. Identifying such strategies, however, has proven challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, prolonged cytopenia due to lymphodepletion chemotherapy before T-cell infusion is a critical concern. Furthermore, previous trials have indicated that different lymphodepletion conditions might affect treatment efficacy 25 . Recently, new CAR-T cells designed with synthetic chimeric receptors with an orthogonal IL-2r extracellular domain fused with an IL-9r intracellular domain have been described, which can also be expanded in the absence of conditioning lymphodepletion 25 .…”
Section: Cellular Therapymentioning
confidence: 99%
“…Although CAR T therapy demonstrates remarkable efficacy in patients with hematological malignancies, the outcomes are limited by the tumor microenvironment (TME), particularly in solid tumors [ 22 ]. However, by repurposing IL-9R signaling using a chimeric orthogonal cytokine receptor, T cells gain new functions including characteristics of stem cell memory and effector T cells leading to augmented anti-tumor activity against solid tumors [ 23 ]. CAR-NK cell therapy has started to gain attraction as an alternative to CAR-T approach.…”
Section: Introductionmentioning
confidence: 99%